Implications of Specified Skilled Workers Visa on Japan’s Health Sector Labor Market Equilibrium - Fitri Adi Setyorini; RR. Zahroh Hayati Azizah (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2026)
The Japanese government introduced the specified skilled worker visa in response to the increasing labor crisis, especially in the health sector. This study uses a quantitative approach to analyze the implications of implementing the specified skilled worker's visa on the labor market balance in the Japanese health sector. The data for this study consists of secondary data obtained from official government reports, scientific publications, and statistics of foreign workers working in the health sector. The data collection technique uses document analysis of these sources. The analytical methods used include descriptive statistical analysis to describe labor trends and inferential analysis to test the hypothesis of the impact of the specified skilled worker's policy on the labor market balance. The results show that the specified skilled worker's visa has successfully reduced the health sector's labor shortage. Still, it also poses new challenges, such as the need for further training and cultural adaptation. In addition, this study shows that although the specified skilled worker's visa provides a short-term solution to the labor crisis, the program's sustainability requires more comprehensive supporting policies. This study contributes to the existing literature by highlighting the importance of integrating foreign workers through continuous training policies and cultural adaptation programs to ensure long-term productivity and labor market balance in the Japanese health sector.